PENGARUH SELF-CONGRUENCE, MATERIALISM, SHOPPING VALUE TERHADAP BRAND ATTACHMENT, COMPULSIVE BUYING DAN SATISFACTION WITH LIFE PADA PAKAIAN BERMEREK DI INDONESIA - Gavrila Selig Yasin; Dudi Anandya (LPPM Institut Pendidikan Nusantara Global, 2023)
This study aims to analyze the effect of self-congruence, materialism, and shopping value on brand attachment, impulsive buying and obsessive-compulsive buying. In addition, this study also examines the effect of impulsive buying on obsessive-compulsive buying and the influence of both forms of buying on satisfaction with life of branded clothing consumers in Indonesia. Data was collected through a survey with 200 respondents from online questionnaires. The respondents of this study are Indonesian people with compulsive tendencies in buying branded clothes. This study uses a structural equation model approach. This study found a positive effect of ideal self-congruence, materialism, and hedonic value on brand attachment; the negative effect of actual self-congruence and the positive effect of materialism on impulsive buying; as well as the positive effect of materialism and the negative effect of utilitarian value on obsessive-compulsive buying. Brand attachment has a positive effect on impulsive buying and impulsive buying has a positive effect on obsessive-compulsive buying. Impulse buying also has a positive effect on satisfaction with life but obsessive-compulsive buying has no significant effect on satisfaction with life.